O samoświadomości tłumacza (na przykładzie autorskich kontrprzekładów) - Bednarczyk, Anna (Zeszyty Cyrylo-Metodiańskie, 2022)
About the Translator’s Self-Consciousness (on the Example of the Author’s Counter-Translations): The paper examines the issue of translator’s self-awareness understood as an individual act of becoming aware of the reasons for and consequences of actions taken, as well as one’s own abilities, rather than as a competence referred to in skills and knowledge. Due to the fact that the latter are relatively often identified by researchers with self-consciousness, the text points to the reflections of philosophers who see this concept both in a broad and narrow sense as related to creative activity. Acknowledging the disconnect between self-consciousness and competence, the author cites not only judgements of theorists, but also examples of counter-translations of a given work in different variants by the same translator. Possible reasons for the creation of successive versions are discussed. The analysis confirms that the re-translation does not always correct the mistakes of the first one, and often turns out to be a response to a demanded, e.g. by the editors, approach to a particular text. This may be related to a different translation goal or to a different function of the target variant. Consequently, the article presents different Polish versions of Russian poems, equivalent from the point of view of lexical-semantic and stylistic adequacy of both texts, but different in terms of pragmatics.